Maternal pre-pregnancy obesity affects the uncinate fasciculus white matter tract in preterm infants - Lee, Joo Young; Lee, Hyun Ju; Jang, Yong Hun; Kim, Hyuna; Im, Kiho; Yang, Seung; Hoh, Jeong-Kyu; Ahn, Ja-Hye (Frontiers in Pediatrics, 2023)
Background: Growing evidence suggests an association between a higher maternal pre-pregnancy body mass index (BMI) and adverse long-term neurodevelopmental outcomes for their offspring.Despite recent attention to the effects of maternal obesity on fetal and neonatal brain development, changes in the brain microstructure of preterm infants born to mothers with pre-pregnancy obesity are still not well understood. This study aimed to detect changes in the brain microstructure in maternal pre-pregnancy obesity and their offspring born as preterm infants using diffusion tensor imaging (DTI).Methods: Thirty-two preterm infants (born to 16 mothers with normal-BMI and 16 mothers with a high-BMI) at < 32 weeks of gestation without brain injury underwent brain magnetic resonance imaging (MRI) at term-equivalent age. The BMI of all pregnant women were measured within approximately the 12 weeks before pregnancy or within the first 2 weeks of gestation. We analyzed the brain volume using a Morphologically Adaptive Neonatal Tissue Segmentation toolbox and calculated the major white matter tracts using probabilistic maps of Johns Hopkins University neonatal atlas. We investigated the differences in brain volume and white matter microstructure between preterm infants of mothers with normal-and high-BMI. DTI parameters were compared among groups using analysis of covariance adjusted for postmenstrual age at scan and multiple comparisons.Results: Preterm infants born to mothers with a high-BMI showed significantly increased cortical gray matter volume (p=0.001) and decreased white matter volume (p=0.003) after controlling for postmenstrual age and multiple comparisons. We found significantly lower axial diffusivity in the uncinate fasciculus compared than mothers with normal-BMI group (1.690±0.066 vs. 1.762±0.101, respectively; p=0.005).Our study is the first to demonstrate that maternal obesity impacts perinatal brain development patterns in preterm infants at term-equivalent age, even in the absence of apparent brain injury. These findings provide evidence for the detrimental effects of maternal obesity on brain developmental trajectories in offspring and suggest potential neurodevelopmental outcomes based on altered uncinate fasciculus white matter microstructure, which is known to be critical for language and social-emotional functions.